Control Efficacy and Deposition Characteristics of an Unmanned Aerial Spray System Low-Volume Application on Corn Fall Armyworm Spodoptera frugiperda - Shan, Changfeng; Wu, Jiajun; Song, Cancan; Chen, Shengde; Wang, Juan; Wang, Haihong; Wang, Guobin; Lan, Yubin (Frontiers in Plant Science, 2022)
As a major global pest, fall armyworm (FAW) Spodoptera frugiperda invaded China in 2019, which has seriously threatened the safety of China's food production and raised widespread concerns. As a new low-volume application technology, an unmanned aerial vehicle (UAV) is playing an important role in the control of FAW in China. However, the studies on the influence of the water application volume on the efficacy of FAW using UAV were limited. In this study, Kromekote® cards were used to sample the deposition. The method of using sampling pole and sampling leaf for the determination of deposition. Four water application volumes (7.5, 15.0, 22.5, and 30.0 L/ha) were evaluated with regard to the corn FAW control efficacy. A blank control was used as a comparison. The control efficacy was assessed at 1, 3, 7, and 14 days after treatment (DAT). The tested results showed that sampling methods have a significant effect on deposition results. The number of spray deposits and coverage on the sampling pole were 35% and 40% higher than those on the sampling leaves, respectively. The deposition and control efficacy gradually increased with the water application volume increased. The control efficacy at 14 DAT under different water application volumes was in the range of 59.4~85.4%. These data suggested that it is possible to use UAV spraying to achieve a satisfying control of FAW, but the control efficacy of the water application volume of 30.0 L/ha and water application volume of 22.5 L/ha did not differ significantly. Considering work efficiency, a water application volume of 22.5 L/ha is recommended for field operation.